Role of Three‐Dimensional Echocardiography in Structural Complications after Acute Myocardial Infarction. Issue 6 (25th March 2014) - Ermacora, Davide; Muraru, Denisa; Pontarollo, Sara; Casablanca, Simona; Livi, Ugolino; Iliceto, Sabino; Badano, Luigi P.
Mini‐Abstract We report 3 emblematic cases which show how three‐dimensional echocardiography (3DE) can provide unique information useful to address management of structural complications in patients with acute myocardial infarction: (1) detailed assessment of size, location, and morphology of an apical ventricular septal defect (VSD) obtained with transthoracic 3DE was pivotal in referring a patient to percutaneous closure; (2) size and location of a complex inferior VSD with irregular margins advised against percutaneous closure; and (3) Transesophageal 3DE assisted surgeons to choose between reparative or replacement surgery for an acute mitral regurgitation due to complete papillary muscle rupture.